Upregulation of GLT-1 via PI3K/Akt Pathway Contributes to Neuroprotection Induced by Dexmedetomidine - Peng, Mengyuan; Ling, Xiaomin; Song, Ruixue; Gao, Xuan; Liang, Zhifeng; Fang, Fang; Cang, Jing (Frontiers in Neurology, 2019)
Perioperative ischemic stroke usually leads to neurological dysfunction caused by neuron death. During the ischemic condition, excitotoxity due to extracellular glutamate accumulation is a main mechanism of neuron damage. The clearance of glutamate mainly depends on glutamate transporter-1 (GLT-1) which is expressed in astrocytes. Dexmedetomidine, an α2 adrenergic receptor agonist, is proved to induce neuroprotection. This study was set out to investigate the glutamate-related mechanism involved in the neuroprotective effect of Dexmedetomidine. Middle cerebral artery occlusion (MCAO) was used as a model of ischemic stroke in our study. We determined Neurological deficit scores (NDS) and Magnetic resonance imaging (MRI) at three points (2h, 6h, and 24h) after middle cerebral artery occlusion (MCAO) to evaluate the neuroprotective effect of Dex. Besides, we performed western blot (6h and 24h after MACO) and immunofluorescent staining (24h after MCAO) to observe the expression of GLT-1. The effect and mechanism of Dexmedetomidine on GLT-1 in primary cultured astrocytes were investigated using western blot and RT-PCR. Our results showed that pretreatment with Dexmedetomidine improved NDS and reduced infarct volume as well as upregulating GLT-1 expression. Furthermore, using Atipamezole and LY294002 ,we found that Dex significantly increased GLT-1 levels in astrocytes via activating α2 adrenergic receptor and PI3K/AKT pathway both in vitro and in vivo study. Overall, our present study indicated that Dex had neuroprotective effects on ischemia stroke and upregulation of GLT-1 levels by PI3K/AKT dependent pathway might be the potential mechanism.